2019
DOI: 10.1002/mrd.23240
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal dependence of cadmium molecular effects on Mytilus galloprovincialis (Lamarck, 1819) protamine‐like protein properties

Abstract: Mussels have a seasonal reproduction and cadmium is a common stressor in estuarine and coastal environments. In previous studies, we have shown that exposure to subtoxic doses of cadmium produced alterations in the properties of winter Mytilus galloprovincialis sperm protamine-like (PL) proteins. In this study, it was analyzed the possibility that these cadmium effects may be seasonal. Winter and summer mussels were exposed to CdCl 2 , and it was tested the PL-proteins for cadmium bioaccumulation, electrophore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 62 publications
(83 reference statements)
0
19
0
Order By: Relevance
“…Cadmium (Cd) is a toxic non-essential transition metal; the third main environmental contaminant of most hazards after mercury and lead. This metal poses a health risk for both humans and animals already at very low concentrations (0.5 µM) [ 2 , 3 , 4 , 5 ], while for plants there is usually a wider range of concentrations (from 5 to 5000 µM) that are generally not phytotoxic to the plants [ 6 , 7 ]. Cd can negatively affect plant growth, and its toxic effects can be found at both morphological and physiological levels [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cadmium (Cd) is a toxic non-essential transition metal; the third main environmental contaminant of most hazards after mercury and lead. This metal poses a health risk for both humans and animals already at very low concentrations (0.5 µM) [ 2 , 3 , 4 , 5 ], while for plants there is usually a wider range of concentrations (from 5 to 5000 µM) that are generally not phytotoxic to the plants [ 6 , 7 ]. Cd can negatively affect plant growth, and its toxic effects can be found at both morphological and physiological levels [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is now well known that, in the coming decades, the loss of biodiversity will have a dramatic impact on the life cycles of organisms [1][2][3]. Anthropogenic human activities and xenobiotics released into the environment such as metals, pesticides, herbicides, drugs, antifouling compounds, nanoparticles, and plastics directly influence migration, seasonal breeding, and reproduction [4][5][6]. These factors also have secondary deleterious effects contributing to climate change, as evidenced in global warming and ocean acidification, raising an alarm in the scientific community and government environmental agencies about reprotoxicity [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, in these latter proteins, some heavy metals can reverse their canonical protective rule, making them able to participate in DNA breakage [ 11 , 34 , 36 , 37 ]. In addition, our studies also indicated that in organisms exposed to environments polluted by heavy metals, we found accumulation of some of these metals in gonadal tissues, semen and SNBP [ 37 , 38 , 39 ]. As a matter of fact, in the semen of the father and son, we found different excesses of copper and chromium, two heavy metals involved in the Fenton reaction [ 40 ].…”
Section: Discussionmentioning
confidence: 63%
“…The binding between histones and chromium happens through lysine residues [ 46 , 47 ] and could cause DNA damage in a similar manner as hypothesized for copper, since the toxic effect of this metal results in radical-mediated DNA strand breakage and the formation of stable chromium–DNA complexes, together with chromium–DNA adducts and protein–chromium–DNA and DNA–chromium–DNA cross-links [ 48 , 49 ]. The unstable DNA bond observed only for son SNBP could be due to the excess of copper, which can also determine conformational change in these proteins, as already demonstrated for protamine-like of mussels exposed to this metal [ 37 , 39 ]. Moreover, the presence of nCP/Hr ratio could also produce a competition between these two types of proteins for DNA binding.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation